2018
DOI: 10.1186/s12879-018-3320-5
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of the seroprevalence to the egg-positive prevalence of Schistosoma japonicum in China: a meta-analysis

Abstract: BackgroundSchistosomiasis, caused by Schistosoma japonicum, remains one of the most important parasitic diseases, and detection of S. japonicum infections in humans plays a crucial role in control and treatment. However, comparisons between the parasitological and the immunological examinations in the fields of China are lacking. Therefore we performed a meta-analysis to compare the seroprevalence of Schistosoma japonicum, as determined by IHA or ELISA, with coprological prevalence, as determined by Kato-Katz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A previous study in China revealed that the prevalence of schistosomiasis japonica determined by serological tests was Â4-5 times higher than that estimated by fecal examination (Deng et al, 2018). This finding implies that the prevalence of S. japonicum is underestimated by stool examination.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A previous study in China revealed that the prevalence of schistosomiasis japonica determined by serological tests was Â4-5 times higher than that estimated by fecal examination (Deng et al, 2018). This finding implies that the prevalence of S. japonicum is underestimated by stool examination.…”
Section: Discussionmentioning
confidence: 84%
“…Schistosoma japonicum is the most prevalent species causing schistosomiasis japonica in Asia, especially in the People's Republic of China, the Philippines and Indonesia (Gordon et al, 2015;McManus et al, 2018;Moendeg et al, 2017;WHO, 2020). In 2015, the number of infected people in China was approximately 77 200, down from the 11.6 million estimated to have been infected when China first implemented its control program in the 1950s (Chen, 2014;Deng et al, 2018). However, a recent serological diagnostic study of approximately 7.2 million people in China found approximately 138 500 schistosomiasis infections (Chen et al, 2021;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Latin America and Southeast Asia, the identified reports addressed the pathophysiology rather than the epidemiology of schistosomiasis during pregnancy [ 4 , 47 ]. However, in these settings in which there are no published articles on schistosomiasis during pregnancy, there are meta-analyses on schistosomiasis available for other age groups [ 48 , 49 ]. Moreover, a previous study on S. japonicum during pregnancy assessed the pathophysiology rather than the prevalence of schistosomiasis during pregnancy [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mature adult worms reside in the mesenteric (S. mansoni and S. japonicum) or pelvic (S. haematobium) veins, where female worms lay eggs that are later secreted in stools or urine. Eggs trapped in the surrounding tissues and organs cause inflammatory immune responses that result in intestinal, hepato-splenic, or urogenital disease [93]. Seventy-eight countries are endemic for schistosome infections, with different species of schistosomes affecting different regions.…”
Section: Schistosomiasismentioning
confidence: 99%